(untitled) (International Journal of Agricultural Research, Innovation and Technology, 2024)
The Fourth Industrial Revolution (4IR) and the concept of the Fourth Agricultural Revolution (4AR) are interconnected, as they both refer to the application of advanced technologies. The Fourth Industrial Revolution has the power to revolutionize agriculture, enabling farmers to embrace innovation, increase productivity, and foster sustainable practices. The purpose of this study was to determine the extent of knowledge and attitude of respondents; to determine the familiarity of the respondents with 4AR technologies, to measure the severity of problems perceived by the respondents concerning 4AR, to find out the suitability of solutions for adopting 4AR innovations and to explore the relationship between each of the selected characteristics of the respondents with the focused issues. Primary data were collected from purposively selected 70 respondents during the period of 1 May, 2023 to 9 May, 2023 at Khulna district through face-to-face discussions and online interviews by using a pre-tested interview schedule. Descriptive statistics such as mean, standard deviation, percentage and Spearman Coefficient of Correlation were measured for data interpretation by using SPSS. Almost 72.9% of the respondents had low knowledge of 4AR technologies and a proportion of 95.7% of the respondents had a favorable attitude toward 4AR. Maximum respondents are highly familiar with the technology of “Using an automated machine for seedling transplantation” and “Using agricultural drones in applying fertilizers and pesticides in crop fields”. The main problem based on the problem severity index was “High initial investment to purchase 4AR technologies”. The best possible solutions according to the solution index were making the 4AR technologies available at low prices in the local market” followed by financial support from the Government and other agencies. Knowledge and attitude towards 4AR technologies had a significant positive relationship with the familiarity of 4AR technologies. Training experience had a highly significant relationship with the determination of associated problems in 4AR implementation. Knowledge of 4AR and training experience had a highly significant positive relationship with the measurement of the suitability of probable solutions. Int. J. Agril. Res. Innov. Tech. 14(1): 77-86, June 2024